2020
DOI: 10.1002/ijgo.13042
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal surveillance for congenital Zika infection during the 2016 microcephaly outbreak in Salvador, Brazil: Zika virus detection in asymptomatic newborns

Abstract: Objective: To identify newborns with congenital Zika infection (CZI) at a maternity hospital in Salvador, Brazil, during the 2016 microcephaly outbreak. Methods: A prospective study enrolled microcephalic and normocephalic newborns with suspected CZI between January and December 2016. Serology (immunoglobulins IgM and IgG) and quantitative reverse transcriptase polymerase chain reaction (RT-qPCR) for the Zika virus were performed. Demographic and clinical characteristics of newborns with and without microcepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…Participants were recruited from a previous neonatal surveillance program for Congenital Zika Infection in 2016 at a public maternity hospital in the municipality of Salvador (Bahia), located in Northeastern Brazil [ 42 ]. All enrolled newborns were classified according to the criteria established by the International Fetal and Newborn Growth Consortium for the 21st Century (INTERGROWTH-21st).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were recruited from a previous neonatal surveillance program for Congenital Zika Infection in 2016 at a public maternity hospital in the municipality of Salvador (Bahia), located in Northeastern Brazil [ 42 ]. All enrolled newborns were classified according to the criteria established by the International Fetal and Newborn Growth Consortium for the 21st Century (INTERGROWTH-21st).…”
Section: Methodsmentioning
confidence: 99%
“…Ethylenediaminetetraacetic acid (EDTA) plasma was obtained by centrifugation and stored at −80 °C until analysis. Serological and molecular ZIKV diagnoses were performed according to previously described methods [ 42 , 44 ]. Congenital Zika was defined when newborns presented positivity upon serological testing (anti-ZIKV immunoglobulin M-IgM) or real-time reverse transcription PCR (rRT-PCR) for ZIKV.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, features of the Brazilian CZS outbreak have become a talking point in relation to the local high concentration of microcephaly cases in northeastern Brazil [ 50 , 51 , 52 , 53 , 54 ]. Campos et al proposed that “the unusual distribution of microcephaly in the Northeast region might be accentuated by prior, sequential exposition and/or co-viral infection with other pathogen”, suggesting that ZIKV is not the only culprit [ 55 , 56 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…More so than the lack of available in vivo models, ZIKV is a biological complex system whose evolution design depends on the meeting of other biological entities, such as through the occurrence of a mixed viral infection in human. Taken together, this leads to the belief that globalization contributes to the intensification of co-exposition, leading to great opportunities for ZIKV outbreaks ( Figure 1 and Figure 3 for ZIKV, latent virus and host) [ 56 , 57 , 58 , 96 ]. ZIKV is an arthropod-borne virus, transmitted especially by Aedes species.…”
Section: Introductionmentioning
confidence: 99%
“…Ocampo et al . showed that newborns of Zika‐infected women were mostly born at full term and with normal birthweight, while de Siqueira et al . emphasized the need for continuous screening of newborns, even among those not exhibiting any symptoms of Zika virus, to ensure timely access to services.…”
mentioning
confidence: 99%